Sostenibilidad, perdurabilidad empresarial y fallo de los servicios: una aproximación al cierre de empresas en el sector turismo - Carlos Alberto Gómez Cano; Verenice Sánchez Castillo (Mundo Fesc)
The concept of "sustainable tourism" presents several challenges for its implementation in business practice. From its specificity and excessive generality to the lack of integration between the variables contained in the different conceptualizations by dimensions and indicators, this concept can end up providing a mechanistic framework for the interpretation of phenomena occurring in the sector, such as business closures and service failures. The study employed a mixed-method design based on an emergent and concurrent strategy. Triangulation of sources, researchers, perspectives, and methods was used as methodological resources to ensure reliability. The main results achieved suggest the need to generate explanatory models that are simultaneously comprehensive. The linearity and mechanistic nature of the interpretations of phenomena in studies determines how they are perceived, which depends on the disciplinary lens. Furthermore, the results suggest that business closures, as a complex phenomenon, must be addressed from integrative perspectives.